2022
DOI: 10.3390/nu14235013
|View full text |Cite
|
Sign up to set email alerts
|

Association between Depression, Anxiety Symptoms and Gut Microbiota in Chinese Elderly with Functional Constipation

Abstract: This study aimed to investigate the relationship between anxiety, depression, and gut microbiota in elderly patients with FC. Methods: in this cross-sectional study, a total of 198 elderly participants (85 male and 113 female) aged over 60 years were recruited. The study was conducted in Changsha city, China. The participants completed an online questionnaire, including The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), The Patient Assessment of Symptoms (PAC-SYM), and The Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“… 8 , 9 This association may be due to the potential gastrointestinal side effects associated with antidepressant treatments 10 or the gut-brain axis pathway mediated by gut microbiota. 11 A longitudinal study on premorbid constipation and later diagnosis of depression may complement the previous evidence from cross-sectional studies. 12 If this physical symptom happens before the onset of depression, it can also be regarded as a potential prodromal symptom.…”
Section: Introductionmentioning
confidence: 81%
“… 8 , 9 This association may be due to the potential gastrointestinal side effects associated with antidepressant treatments 10 or the gut-brain axis pathway mediated by gut microbiota. 11 A longitudinal study on premorbid constipation and later diagnosis of depression may complement the previous evidence from cross-sectional studies. 12 If this physical symptom happens before the onset of depression, it can also be regarded as a potential prodromal symptom.…”
Section: Introductionmentioning
confidence: 81%
“…Al-Jassas et al also proved COVID-19 infected patients accompanied by lung lesions and low 2 might exert neuropsychiatric symptoms, due to the activation of immune-inflammatory pathways (30). Studies also showed that depressed people had a higher risk of constipation and vice versa, which might due to inflammation, immune abnormalities, energy metabolism, gut microbiota, and metabolites, like choline, betaine, and glycine (31)(32)(33)(34). In recent years, a large number of research on medical models has been conducted globally to improve the treatment effectiveness and patients' quality of life.…”
Section: Somatic Discomfort and Sleep Disorders Are Risk Factors For ...mentioning
confidence: 99%
“…Long-term constipation will not only lead to colon diverticulum, perianal disease, colon melena, and other anorectal diseases (11), but also become a common predisposing factor for cardiovascular and cerebrovascular diseases such as myocardial infarction and cerebrovascular accident (12,13). Some patients with severe constipation can also suffer from psychological disorders such as insomnia, irritability, depression, and obsessive-compulsive thoughts and behaviors (14)(15)(16). Therefore, as the aging of the population increases, this disease will seriously affect patients' quality of life and bring a heavier burden to society.…”
Section: Introductionmentioning
confidence: 99%